Exploring the relationships between CT and pathological characteristics and gene mutations in neoplastic ground glass nodules - Zi-ya Zhao; Si-zhu Liu; Xue-ping Chen; Yang-li Zhang; Bin-jie Fu; Wang-jia Li; Fa-jin Lv; Zhi-gang Chu (BMC Medical Imaging)
Abstract Background Neoplastic ground glass nodules (GGNs) are relatively indolent tumors, with slow progression in invasiveness and computed tomography (CT) features. This study aimed to explore the correlation between pathological and CT characteristics and gene mutations in neoplastic GGNs. Methods We retrospectively analyzed 1,348 neoplastic GGNs from January 2019 to November 2022, including 290 adenocarcinomas in situ (AIS), 448 microinvasive adenocarcinomas (MIA), and 610 invasive adenocarcinomas (IAC). The correlations between patients’ characteristics, pathological subtypes and grades, CT features, changes in follow-up, and gene mutations were analyzed. Results Solid component (odds ratio [OR] = 1.493; P = 0.014), larger size (OR = 1.049; P = 0.006), ill-defined boundary (OR = 1.368; P = 0.027), and lobulation sign (OR = 1.824; P = 0.001) were revealed as independent CT predictors of gene mutation. From AIS to IAC, the epidermal growth factor receptor (EGFR) mutation rate significantly increased (P < 0.01), while the kirsten rat sarcoma viral oncogene (KRAS) and the anaplastic lymphoma kinase (ALK) mutation rates significantly decreased (P < 0.05). Among IACs, mutation rate was the highest in the intermediate-grade ones (P < 0.05). Gene mutations were more frequently detected in nodules showing changes during follow-up (76.3% vs. 61.1%, P = 0.02), especially in those with more than 2-year follow-up (77.1% vs. 43.7%, P = 0.023). However, the specific changes were not associated with gene mutations (P = 0.273). Conclusions Gene mutations in neoplastic GGNs were associated with CT features, pathological subtypes and grades, and changes observed during long-term follow-up.